ANALYSIS IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT ON THE PERFORMANCE OF STATE CIVIL APPARATUS IN THE NORTH MINAHASA DISTRICT GOVERNMENT - Jan, Arrazi Hasan; Tumbuan, Willem Jfa; Palandeng, Indrie Debbie (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Basically, agencies do not only need capable and skilled ASN. Agencies really need ASN who can work harder and have the desire to achieve optimal results in accordance with the goals of the agency. Agency support for the abilities possessed by employees is important, considering that the agency environment, both internal and external, will always experience continuous change. ASN is one of the very important factors that cannot be separated from an organization, especially an institution. ASN is also the key that determines the development of an institution. In essence, ASN is a human being who is employed in an organization as a driver to achieve the goals of the organization. Therefore, ASN must be managed properly to increase the level of effectiveness and efficiency in the organization. Activities that are often found in ASN are stimulating, developing, motivating, and maintaining high performance within the organization and all activities carried out in ASN do not conflict with the norms that apply in society. Improving the performance of the State Civil Apparatus must be improved to support success in an institutional organization, improving its human resources must also be considered.